Problems of Editing in the Italian Translation of Noam Chomsky’s The New Military Humanism — Lessons from Kosovo: A Case Study - Fusari, Sabrina (Meta, 2002)
AbstractIn this paper, I discuss a number of problems that arise in the relationship between free-lance translators and in-house editors in the publishing sector. In the first part, I discuss the general problems that may arise when a translation is revised by in-house editors. In the second part of my paper, I analyse the characteristics of translators’ mistakes. I then discuss a case study, i.e., problems in the editing of the Italian translation of Noam Chomsky’s The New Military Humanism. In the fourth and last part, I draw some general conclusions and propose ways to change the relationship between translators and publishing houses in order to improve the working conditions of translators as well as the quality of publications.